Strategi Pembangunan Desa Di Daerah Tertinggal Pada Kawasan Konservasi Bukit Rimbang Bukit Baling Desa Batu Sanggan - Samsi Nurzaman; Arief Rifa'i (UIR Press, 2019)
The implementation of village development is a form of implementation of the form of implementation of development programs in the form of multidimensional as a form of the implementation of the State's objectives in achieving the implementation of village development. It aims to make development policies truly strategic. The geographical shape of the area of Indonesia influences the development policies to be taken, as does the development of villages in conservation areas. Because it involves the regulation of conservation area regulations so that any form of development must be in accordance with the provisions of the Conservation Area Act. Batu Sanggan Village is a village located in the Bukit Rimbang Bukit Baling Conservation area. This is a special concern about the Analysis of Development Strategies that will be carried out, because basically the development carried out in general is not the same as development in other villages. Thus the need for a village development strategy that is analyzed in depth so that this is sought in analyzing what forms of development can be carried out in the conservation area, so that this is expected to realize an equitable and equitable development achievement. However this cannot be done optimally, in essence it concerns overlapping regulations regarding village development with conservation area regulations, so that the most very sad is that all forms of village planning and development are hampered due to the Batu Sanggan village problem which is located in the conservation area.